AI-Driven Big Data Processing on Cloud Platforms for Predictive Financial Decision-Making (International Journal of Engineering & Extended Technologies Research (IJEETR), 2026)
The rising complexity and magnitude of financial information in the modern digitalized world have indeed led to the application of superior technologies that enhance decision-making. This study paper discusses how Artificial Intelligence (AI) and Big Data processing can be implemented to cloud environments to improve predictive financial decision-making. The combination of AI and the cloud-based big data systems is highly promising in streamlining the financial analytics, through the provision of real-time insights, enhancing the accuracy, and lowering the operational costs. The suggested framework uses the infrastructure of cloud computing to store and to process huge amounts of financial data and uses machine learning and data mining strategies to forecast the trends, risks, and opportunities in the financial markets. The AI algorithms implemented in the structure improve the capacity to study past financial data, trace the patterns, and predict the future trends in the market. The most important to note about the frameworks are the data collection, data preprocessing, model training, predictive analytics and decision-making support, which are all supported by a scalable cloud environment. This practice will enable greater flexibility and responsiveness to the changing market circumstances, making informed financial choices. The study also shows the problems and constraints of such systems implementation, such as the data privacy issue, model interpretability, and the issue of managing cloud resources. This article provides a new paradigm of data-driven strategy in the financial industry by showing the effectiveness of AI-based big data solutions in changing the financial decision-making process through case studies and experimental findings.
Keywords: Artificial Intelligence; Big Data; Cloud Computing; Predictive Analytics; Financial Decision-Making; Machine Learning; Data Mining